African regional and national burden of diabetes mellitus and its attributable risk factors from 1990 to 2021: results from the global burden of disease study 2021 - Wang, Qiu-Yun; Mensah, Emmanuel; Li, Zhi-Chao; Wang, De-Guo; Zhang, Cui-Wei; Baako, Bruno Miezah; Zha, Lei; Kong, Xiang (Frontiers in Endocrinology, 2025)
AimsDiabetes mellitus (DM), a chronic disease characterized by hyperglycemia, has become a global health concern. This study evaluates the burden of DM in the African region from 1990–2021 to inform prevention and control strategies.MethodsUtilizing data from the Global Burden of Disease (GBD) 2021, we analyzed the incidence, prevalence, mortality, disability-adjusted life years, age-standardized rates and estimated annual percentage changes of DM, type 1 DM (T1DM) and type 2 DM (T2DM) in the African region. Decomposition analysis was utilized to explore the contributions of population growth, aging and epidemiological changes to the disease burden. The comparative risk assessment framework was employed to estimate the influence of second-level risk factors on the diabetes burden.ResultsFrom 1990 to 2021, the disease burden of DM, T1DM and T2DM in the African region increased significantly. The age-standardized incidence rate of DM, T1DM and T2DM increased from 157.284, 5.934 and 151.350 per 100,000 population in 1990 to 250.459, 5.987 and 244.472 per 100,000 population in 2021, respectively. The age-standardized prevalence rate for DM, T1DM and T2DM increased from 2,426.585, 185.366 and 2,241.219 per 100,000 population in 1990 to 4,677.459, 189.384 and 4,488.075 per 100,000 population in 2021. The age-standardized mortality rate for DM and T2DM increased from 39.568 and 38.649 per 100,000 population in 1990 to 44.860 and 44.193 per 100,000 population in 2021. The age-standardized disability-adjusted life years(DALYs)for DM and T2DM increased from 1,123.079 and 1,059.430 per 100,000 population in 1990 to 1,379.240 and 1,329.440 per 100,000 population in 2021. Population growth was identified as the key driver of the increasing disease burden. High body mass index was a major risk factor for DALYs in DM/T2DM. Suboptimal temperature was a major risk factor for DALYs in T1DM. Mauritius had the highest incidence and prevalence rates for DM, T1DM and T2DM, while Kenya and Niger exhibited the lowest rates for DM/T2DM and T1DM, respectively.ConclusionDiabetes mellitus (DM) imposes a substantial global disease burden across Africa, necessitating urgent public health interventions to address risk factors and enhance prevention and control measures.